2021
DOI: 10.18553/jmcp.2021.20501
|View full text |Cite
|
Sign up to set email alerts
|

Costs and health resource use in patients with X-linked myotubular myopathy: insights from U.S. commercial claims

Abstract: BACKGROUND: In X-linked myotubular myopathy (XLMTM), mutations in the MTM1 gene result in absence or dysfunction of myotubularin, a protein required for normal development, maintenance, and function of skeletal muscle. Extreme muscle weakness results in severe respiratory failure that is fatal for approximately half of XLMTM-affected children by age 18 months.Most surviving patients require invasive mechanical ventilation, feeding tubes, and wheelchairs for mobility, due to profoundly impaired motor function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…First hospitalization between 0 and 4 years of age for 80% of patients in our study supports Sack et al’s estimate of mean monthly per patient direct medical costs being highest in the first year of life ($74,831), with declining costs over the second, third, and fourth years of life ($23,207, $13,044, and $9,440, respectively) [ 11 ]. In addition, inpatient admissions ($69,025) accounted for the majority of the mean monthly per patient direct medical costs [ 11 ]. Both studies identified the major burden of ventilator support and ventilation management.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…First hospitalization between 0 and 4 years of age for 80% of patients in our study supports Sack et al’s estimate of mean monthly per patient direct medical costs being highest in the first year of life ($74,831), with declining costs over the second, third, and fourth years of life ($23,207, $13,044, and $9,440, respectively) [ 11 ]. In addition, inpatient admissions ($69,025) accounted for the majority of the mean monthly per patient direct medical costs [ 11 ]. Both studies identified the major burden of ventilator support and ventilation management.…”
Section: Discussionsupporting
confidence: 88%
“…Our claims analysis expands on the findings from an economic analysis by Sacks et al showing very high medical costs and intense healthcare resource utilization associated with caring for patients with XLMTM [ 11 ]. First hospitalization between 0 and 4 years of age for 80% of patients in our study supports Sack et al’s estimate of mean monthly per patient direct medical costs being highest in the first year of life ($74,831), with declining costs over the second, third, and fourth years of life ($23,207, $13,044, and $9,440, respectively) [ 11 ]. In addition, inpatient admissions ($69,025) accounted for the majority of the mean monthly per patient direct medical costs [ 11 ].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations